Conserved stem–loop structures in the HIV-1 RNA region containing the A3 3′ splice site and its cis-regulatory element: possible involvement in RNA splicing - Jacquenet, Sandrine (Oxford University Press, 2001)
The HIV-1 transcript is alternatively spliced to over 30 different mRNAs. Whether RNA secondary structure can influence HIV-1 RNA alternative splicing has not previously been examined. Here we have determined the secondary structure of the HIV-1/BRU RNA segment, containing the alternative A3, A4a, A4b, A4c and A5 3′ splice sites. Site A3, required for tat mRNA production, is contained in the terminal loop of a stem–loop structure (SLS2), which is highly conserved in HIV-1 and related SIVcpz strains. The exon splicing silencer (ESS2) acting on site A3 is located in a long irregular stem–loop structure (SLS3). Two SLS3 domains were protected by nuclear components under splicing condition assays. One contains the A4c branch points and a putative SR protein binding site. The other one is adjacent to ESS2. Unexpectedly, only the 3′ A residue of ESS2 was protected. The suboptimal A3 polypyrimidine tract (PPT) is base paired. Using site-directed mutagenesis and transfection of a mini-HIV-1 cDNA into HeLa cells, we found that, in a wild-type PPT context, a mutation of the A3 downstream sequence that reinforced SLS2 stability decreased site A3 utilization. This was not the case with an optimized PPT. Hence, sequence and secondary structure of the PPT may cooperate in limiting site A3 utilization.